Study on the electrical equivalent circuit model of lightning fault cause in power grid system - Asman, Saidatul Habsah; Zainul Abidin, Aidil Azwin; Mohd Ngah, Nurul Ainatul Rahmah; Ab Aziz, Nur Fadilah; Ab. Kadir, Mohd Zainal; Ahmad Mustafa, Nur Badariah; Leong, Yeng Weng (IEEE, 2022)
Transmission line systems are exposed to various fault causes that can reduce the grid performance. One of the fault causes is due to lightning strike. The judgement of the lightning fault cause is usually done after the tripping is detected by the protection operation system and its consume time. Another method to conclude the lightning fault cause is detected using lightning map sensor but, the supplement method is quite expensive and did not employed in the whole grid system in Malaysia. Furthermore, the grid systems are utilized with the Digital Fault Recorder (DFR) as an intelligent electronic device to detect and restore the fault data. By using the voltage and current waveform data obtained from the DFR, the fault behavior could be studied. Therefore, in this paper, an equivalent circuit model has been investigated to understand the correlation between the fault phenomena due to lightning and its voltage and current profile acquired from the DFR.